A vindication of transnational democratic education – replies to Michael Festl, Martin Beckstein and Michael Geiss. Issue 3 (4th December 2020) - Culp, Julian
ABSTRACT: In Democratic Education in a Globalized World (Routledge, 2019) I defend a discourse theory of global justice as the appropriate normative 1 ground for conceiving educational justice and citizenship education under conditions of economic and political globalization. In addition, I articulate democratic conceptions of global educational justice and citizenship education that recognize a moral-political right to democratically adequate education and call for the creation of transnational democratic consciousness. Based on these conceptions I spell out school practices such as historically informed, cross-cultural learning within socially diverse settings that would contribute to realizing these conceptions. In this article I reply to liberal perfectionist, communitarian-conservative and empiricist-historical critiques of Democratic Education in a Globalized World from Michael Festl, Martin Beckstein and Michael Geiss, respectively. I emphasize the feasibility of injustice-reducing educational practices, I explain how a discourse theory of justice accommodates considerations of both the good and the right, and I justify why the grim record of past educational experience does not render pointless the pursuit of progressive aims through education.